Importance of the FcγRIIa-Arg/His-131 Polymorphism in Heparin-induced Thrombocytopenia Diagnosis - Bachelot-Loza, Christilla; Saffroy, Raphaël; Lasne, Dominique; Chatellier, Gilles; Aiach, Martine; Rendu, Francine (Thrombosis and Haemostasis, 1998)
Heparin-induced thrombocytopenia (HIT) involves heparin-dependent antibodies which induce platelet activation. In the present study, we searched for a relationship between the polymorphism of the Fc receptor (FcγRIIa) and the development of HIT. In this purpose, all the donors were genotyped for their FcγRIIA and HIT patients were selected on the basis of at least one positive answer by 14C-serotonin release assay (SRA). The frequency distribution of the FcγRIIa polymorphism in the HIT patient group was similar to that observed in the healthy control group. Moreover, a statistical analysis taking into account our results and those of 3 previously published studies, suggested at most only a weak association between HIT and the FcγRIIa-131 polymorphism.Laboratory tests used to diagnose HIT rely on the activation of normal donor platelets but fail to detect every HIT positive patient. We determined the role of FcγRIIa-131 polymorphism on the reactivity of control platelets to HIT plasmas. When control platelet FcγRIIa-131 was of Arg/Arg form, only 47% of the HIT plasmas were positive by SRA, compared to 81% and 74% for His/His or His/Arg forms, respectively. We also compared the level of anti PF4/heparin antibodies in the HIT plasmas with the response obtained by SRA. The mean anti PF4/heparin antibodies level in HIT plasma was significantly lower in negative SRA than in positive tests when using control platelets from FcγRIIa-Arg/Arg131 and heterozygous donors. Thus, the variability of control platelets to respond to HIT plasmas in the SRA test is related to both the FcγRIIa-131 polymorphism, and to the amount of anti PF4/heparin antibodies.